His Only Wife : A Novel - Medie, Peace A. (Chapel Hill : Algonquin Books of Chapel Hill, 2020)
"An intelligent and funny debut about a relatable, indomitable heroine: a young seamstress in Ghana who agrees to an arranged marriage, only to realize that some compromises are too extreme to accept, illuminating what it means to be a woman in a rapidly changing world"--
Keywords: Marriage -- Fiction -- Ghana; Women -- Fiction -- Social conditions -- Ghana